Case Report: Ipilimumab-Induced Panhypophysitis: An Infrequent Occurrence and Literature Review - Barnabei, Agnese; Carpano, Silvia; Chiefari, Alfonsina; Bianchini, Marta; Lauretta, Rosa; Mormando, Marilda; Puliani, Guilia; Paoletti, Giancarlo; Appetecchia, Marialuisa; Torino, Francesco (Frontiers in Oncology, 2020)
Abstract Background: Immune checkpoint inhibitors (ICIs), by unleashing the anticancer response of the immune system, can improve survival of patients affected by several malignancies, but may trigger a broad spectrum of adverse events, including autoimmune hypophysitis. ICI-related hypophysitis mainly manifests with anterior hypopituitarism, while the simultaneous involvement of both anterior and posterior pituitary (i.e., panhypophysitis) has rarely been described. Case Presentation: In June 2015, a 64-year-old man affected by liver metastases of a uveal melanoma was referred to us due to polyuria and polydipsia. Two months prior, he had started ipilimumab therapy (3 mg/kg iv every 21 days). The treatment was well tolerated (only mild asthenia and diarrhea were reported). A few days before the fourth cycle, the patient complained of intense headaches, profound fatigue, nocturia, polyuria (up to 10 liters urine/daily), and polydipsia. Laboratory tests were consistent with central adrenal insufficiency, hypothyroidism, and transient diabetes insipidus. The pituitary MRI showed an enlarged gland with microinfarcts, while the hypophyseal stalk was normal, and the neurohypophyseal 'bright signal' in T1 sequences was not detected. The treatment included dexamethasone (then cortisone acetate at replacement dose), desmopressin, and levothyroxine. Within the next five days, the symptoms resolved, and blood pressure, electrolytes, glucose, and urinalysis were stable within the normal ranges; desmopressin was discontinued while cortisone acetate and levothyroxine were maintained. The fourth ipilimumab dose was entirely administered in the absence of further side-effects. Conclusion: As ICIs are increasingly used as anticancer agents, the damage to anterior and/or posterior pituitary can be progressively encountered by oncologists and endocrinologists in their clinical practice. Patients on ICIs and their caregivers should be informed about that risk and be empowered to alert the referring specialists early, at the onset of panhypopituitarism symptoms, including polyuria/polydipsia.